2004
DOI: 10.1111/j.1744-7429.2004.tb00316.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Genetic Structuring among Tropical Brazilian Wood Stork Populations and Low Genetic Differentiation from North American Populations

Abstract: The Wood Stork (Mycteria americana) is a wading bird inhabiting subtropical and tropical regions of the American continent. This species is considered endangered in the United States. We compared variability and genetic structuring of nine Brazilian Pantanal subpopulations with an North American population using eight allozyme loci data (MPI, ICD, NSP, EST‐D, LDH, PGM, 6PGD, and PEP‐A) and four microsatellite loci data (WS1, WS2, WS4, and WS6). Average expected heterozygosity of Pantanal population was similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 16 publications
(9 reference statements)
3
13
1
Order By: Relevance
“…Similarly, Wood Stork population analyses revealed no statistical differences in genetic diversity between the threatened southeastern US breeding populations and those of the Pantanal (Tomasulo-Seccomandi, 2004). The lack of difference in genetic variability levels between Wood Stork samples collected in these two areas was also reported in previous studies based on allozymes and four different microsatellite loci (Del Lama et al, 2002;Rocha et al, 2004). Expansions of Jabiru Stork variability analyses indicated that the Pantanal samples exhibited no significant differences when compared to both northern South American population (Venezuela and Guyana) or to the endangered Central American (Belize) population (Lopes et al, unpublished data).…”
Section: Demographic Historysupporting
confidence: 81%
“…Similarly, Wood Stork population analyses revealed no statistical differences in genetic diversity between the threatened southeastern US breeding populations and those of the Pantanal (Tomasulo-Seccomandi, 2004). The lack of difference in genetic variability levels between Wood Stork samples collected in these two areas was also reported in previous studies based on allozymes and four different microsatellite loci (Del Lama et al, 2002;Rocha et al, 2004). Expansions of Jabiru Stork variability analyses indicated that the Pantanal samples exhibited no significant differences when compared to both northern South American population (Venezuela and Guyana) or to the endangered Central American (Belize) population (Lopes et al, unpublished data).…”
Section: Demographic Historysupporting
confidence: 81%
“…Previous studies of the genetic structure of the wood stork Pantanal breeding colonies using nuclear genetic markers showed no genetic differentiation and a high level of gene flow among breeding colonies (Del Lama et al, 2002;Rocha et al, 2004) which led investigators to conclude that all the wood stork Pantanal colonies belong to a single panmictic population and that distance did not represent a significant barrier to gene flow among colonies in the same region. Our AMOVA showed no differentiation among wood stork colonies in the Pantanal.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies investigated the spatial patterns of variation and genetic differentiation among wood stork colonies using nuclear DNA markers (Stangel et al, 1990;Van Den Bussche et al, 1999;Del Lama et al, 2002;Rocha et al, 2004). Allozyme (Stangel et al, 1990), microsatellite, and DNA fingerprint-ing analyses (Van Den Bussche et al, 1999) have indicated low levels of genetic differentiation among wood stork colonies in the US, and the authors speculated that these patterns were the result of recent colonization and high gene flow.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous comparisons of genetic variability and differentiation among wood stork colonies sampled in the US and Brazil have used nuclear DNA markers (Del Lama et al, 2002;Rocha et al, 2004). Analyses of these markers showed similar levels of genetic variability between the two regions using allozymes (Del Lama et al, 2002) and/or microsatellites (Rocha et al, 2004).…”
Section: Introductionmentioning
confidence: 99%